Ending Poverty : How Health and Innovation Can Lead the Way - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank, discusses seeking transformative solutions to challenges of development and poverty that are necessarily cross disciplinary and what a great university should be doing. He talks about the investments that developing countries can make in the health and education of their people which will help reduce extreme poverty in the countries. He speaks about the importance of early childhood development. He talks about stronger health systems in developing countries that can extend the reach of doctors and nurses, and serve as disease outbreak alert and response networks critical to containing infections. He concludes by saying that the pregnant woman who lives in a conflict zone should be focused and we must do whatever it takes to support her so that her newborn child will have a world of opportunity, equal to that of any child in the world.